Exploration of Student Experience in TGT Type Cooperative Learning in Islamic Cultural History (SKI) Subject at MTs Marfu'ah Palembang - Zulhijra, Zulhijra; Wulandari, Septi; Salsabilla, Sausanningtyas Aulia; Putri, Raisya Alifiah (Yayasan Pendidikan Bima Berilmu, 2024)
This research aims to explore students' experiences in cooperative learning of Team Games Tournament (TGT) type in the subject of Islamic Cultural History (SKI) at MTs Marfua'h Palembang. This research method uses a qualitative approach with observation and interviews to understand how students interact and learn in TGT cooperative learning. The results showed that applying TGT can increase students' interest in learning and learning outcomes. Students participating in TGT activities tend to be more active and motivated in understanding SKI material. However, obstacles were also found, such as difficulties in grouping students with heterogeneous academic abilities, lack of preparation and learning motivation, and the need for teacher assertiveness in managing tournament implementation time. Thus, this study contributes to developing more effective and enjoyable learning strategies for students and providing suggestions for teachers to improve the quality of SKI learning through a more optimal application of TGT.